Efficacy and safety of topiramate for reducing impulsivity: A transdiagnostic systematic review and meta‐analysis of a common clinical use. (10th August 2021) - Chapron, Sophie‐Athéna; Nourredine, Mikail; Dondé, Clément; Haesebaert, Frédéric; Micoulaud‐Franchi, Jean‐Arthur; Geoffroy, Pierre Alexis; Rolland, Benjamin
Abstract: Impulsivity is an important transdiagnostic feature of many psychiatric disorders, as well as a marker of poorer outcome. Topiramate is broadly used for reducing impulsivity in various neuropsychiatric disorders, but no systematic review or meta‐analysis has ever explored whether evidence supports this clinical use. We conducted a systematic review and meta‐analysis of the literature, using PubMed, PsycInfo and Cochrane databases. We included all studies assessing the efficacy of topiramate in adults with high levels of impulsivity, based on either psychometric or neuropsychological measures. Seven articles were included, involving 578 participants. Important heterogeneity in designs and quality features was observed. Topiramate lowered impulsivity levels in two of the studies that used the Barratt Impulsiveness Scale (BIS) (401 participants) and in one of the studies that used neuropsychological measures (63 participants). Four other studies found no effect of topiramate on impulsivity. A larger reduction in the BIS‐11 overall score, with a mean difference of 2.57 (95% confidence interval −4.12 to −1.02), was found in the topiramate group than the placebo group using a random effects model. However, one study accounted for the major part (85.5%) of it, and most included studies presented a high risk of bias. The use of a self‐assessment scale induced an additional risk of self‐report bias. No clear‐cut evidence was found for a transdiagnostic effectiveness of topiramate in reducing impulsivity levels. However, encouraging results were found in some specific disorders.